Intertextual Reading of Qisas in Q.S. Al-Maidah: 32–33: A Comparative Analysis of Islamic Scholars and Orientalists - Yardho, Moh.; Bahari, Fadhil Achmad Agus; Rohman, Abdul (Jurnal Ushuluddin, 2025)
Qiṣāṣ is a legal principle that existed in pre-Islamic religions, and in Surah Al-Maidah (5:32-33), the law of qiṣāṣ intersects with Biblical sources. However, the intertextual readings by mufasirun (Qur'anic commentators) are often disproportionate. Additionally, the concept of Orientalist intertextual analysis has created a disconnect with the field of ‘ulūm al-Qur'ān (sciences of the Qur'an), which has implications for the interpretation of these verses. This article aims to explore the Qur'ān's stance on the Biblical tradition in the context of qiṣāṣ through intertextual analysis, applying the principles of ‘ulūm al-Qur'ān. As part of a literature review, the primary source, Surah Al-Maidah (5:32-33), will be examined alongside secondary sources, including scholarly and Orientalist interpretations, to enhance the analysis. This study employs the qualitative data analysis method developed by Miles and Huberman, which involves data condensation, data presentation, and conclusion/verification. This article demonstrates that the Qur'ān engages with the Biblical tradition in two significant ways: 1) It affirms qiṣāṣ as a law that is already present in Abrahamic religious texts, specifically in Leviticus and the Mishnah Sanhedrin. This affirmation highlights the Qur'ān's intertextual connection with the broader Biblical tradition; 2) The Qur'ān revises the earlier concept of qiṣāṣ in the context of a critique directed at the ahl al-Kitāb of Medina and a condemnation of the behaviors characteristic of the Jahiliyya Arabs. Furthermore, Qur'an 5:32 can be interpreted as a foundational principle for the application of diyat in Islamic law, distinguishing it from previous qiṣāṣ laws